KARAKTERISTIK HABITAT KEPITING BAKAU (Scylla sp.) DI EKOSISTEM MANGROVE SILANG CADEK KECAMATAN BAITUSSALAM KABUPATEN ACEH BESAR, PROVINSI ACEH - Mimie Saputri; Muammar Muammar (Biotik, 2018)
Research on the characteristics of Mangrove Crab Habit (Scylla sp) in Silang Cadek Mangrove Ecosystem, Baitussalam Subdistrict, Aceh Besar District, Aceh Province. This study aims to determine the habitat characteristics of Mangrove Crab (Scylla sp) in the Mangrove Ecosystem of Silang Cadek. The research method is survey with purposive sampling technique. The results of the survey are described. The results of the research showed that the water temperature data ranged from 22 s.d 25°C, the pH ranged from 7.5 to 7.7, the water salinity ranged from 30‰ -34‰. Substrate loamy sand, sandy loam, sandy clay loam. There are 4 constituent species of mangrove plants namely Bruguiera gymnorrhiza, Rhizopora stylosa, Rhizopora apiculata, Avicennia marina. Macrozoobenthos found were Nerita lineata, Uca crassipes, Terebralia palustris, Terebralia sulcata, Isognomon ephippium, Saccostrea cucculata, Uca demani, Scylla serrata, Scylla olivacea, Scylla paramamosain.